1998
DOI: 10.1038/sj.hdy.6884320
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of DNA repetitive sequences to mitotic and meiotic chromosomes of Brassica oleracea var. alboglabra by fluorescence in situ hybridization

Abstract: As part of a programme to integrate the genetic and physical chromosome maps of Brassica oleracea we have carried out fluorescence in situ hybridization (FISH) to mitotic and meiotic chromosomes of B. oleracea var. alboglabra, using repeat sequence DNA probes. We have confirmed that there are three 18S-5.8S-25S rDNA sites in the haploid genome and accurately determined their locations for the first time; two occur subtelomerically on the short arms of the two satellited acrocentric chromosomes (chromosomes 4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Robust molecular cytogenetic karyotypes established for B. rapa, B. oleracea, and B. napus: Numerous molecular cytogenetic studies have reported karyotypes in diploid and amphidiploid Brassica species on mitotic metaphase complements and meiotic prophase (pachytene) chromosomes (e.g., Armstrong et al 1998, Fukui et al 1998Snowdon et al 2002;Koo et al 2004;Lim et al 2005Lim et al , 2007Maluszynska and Hasterok 2005;Howell et al 2008;Kim et al 2009;Mun et al 2009). Among the crop species in the Brassicaceae, the B. rapa genetic, physical, and cytogenetic maps have begun to be integrated by BAC-FISH (Koo et al 2004;Lim et al 2005Lim et al , 2007Yang et al 2007;Kim et al 2009;Mun et al 2009;Xiong et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robust molecular cytogenetic karyotypes established for B. rapa, B. oleracea, and B. napus: Numerous molecular cytogenetic studies have reported karyotypes in diploid and amphidiploid Brassica species on mitotic metaphase complements and meiotic prophase (pachytene) chromosomes (e.g., Armstrong et al 1998, Fukui et al 1998Snowdon et al 2002;Koo et al 2004;Lim et al 2005Lim et al , 2007Maluszynska and Hasterok 2005;Howell et al 2008;Kim et al 2009;Mun et al 2009). Among the crop species in the Brassicaceae, the B. rapa genetic, physical, and cytogenetic maps have begun to be integrated by BAC-FISH (Koo et al 2004;Lim et al 2005Lim et al , 2007Yang et al 2007;Kim et al 2009;Mun et al 2009;Xiong et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several karyotypes have been published for Brassica species on the basis of different staining methods, such as Giemsa staining, C-banding, CMA3/ 49-6-diamidino-2-phenylindole (DAPI) fluorescent staining, silver staining, and fluorescence in situ hybridization (FISH) with rDNA or pericentromeric tandem repeats (Olin-Faith and Hennen 1992;Maluszynska and Heslop-Harrison 1993;Cheng et al 1995;Snowdon et al 1997;Armstrong et al 1998;Fukui et al 1998;Hasterok et al 2001Hasterok et al , 2005Hasterok et al , 2006Howell et al 2002;Kulak et al 2002;Snowdon et al 2002;Ziolkowski and Sadowski 2002;Koo et al 2004;Maluszynska and Hasterok 2005;Lim et al 2005Lim et al , 2007. However, given the lack of specific chromosomal markers, even the best karyotypes developed could distinguish only six chromosomes in diploid B. rapa and three chromosomes in diploid B. oleracea.…”
mentioning
confidence: 99%
“…Westar and N-o-1, a DH line derived from Westar (provided by John Innes Centre, Norwich, UK). Methods for staging and fixing anthers have been described previously (Armstrong et al 1998;Howell et al 2002). Slides were prepared from these anthers following enzyme digestion (Armstrong et al 1998;Howell et al 2002) but cytohelicase was omitted from the enzyme mixture and the digestion time was extended to 2 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Slide preparations and FISH: Slide preparations were made from individual anthers and root tips, adjusting the digestion time as necessary (Armstrong et al 1998;Howell et al 2002). Methods for the slide pretreatment, hybridization, and posthybridization procedures for FISH have been described previously (Howell et al 2002).…”
Section: Methodsmentioning
confidence: 99%